Distribusi komposisi ukuran dan pola pertumbuhan Ikan Selar Kuning (Selaroides leptolepis) di Perairan Utara Manokwari - Ridwan Sala; Roni Bawole; Rizki H. Karamoy (Cassowary, 2022)
The status of yellow trout fish resources in the northern waters of Manokwari until now has not been known with certainty regarding the distribution of size composition and growth patterns. This study was conducted to determine the frequency distribution in length and weight of yellow trout (S. leptolepis), the relationship between length and weight of yellow trout (S. leptolepis) and the growth pattern of the yellow trout in the northern waters of Manokwari. This research was carried out in a boat chart that made the landing of yellow trout fish at the Sanggeng Landing Fish Base (PPI) in Manokwari Regency and was carried out for 2 different months between May and July 2021. From the results of the analysis, it was found that the highest frequency distribution of S. leptolepis in May was in class range 16.24 – 16.82 cm with a total of 523 individuals, while in July the highest frequency of length was found in the class range 15.06 – 15.64 cm. The relationship between length and weight of yellow trout in the waters of North Manokwari has the equation W = 0.0533L2.4759, where length growth affects weight growth with R2 = 0.7436, meaning that the growth of yellow trevally in North Manokwari waters is allometric negative.